Numerical Simulations for a Typical Train Fire in China. (21st March 2011) - Chow, W. K.; Lam, K. C.; Fong, N. K.; Li, S. S.; Gao, Y.
Abstract : Railway is the key transport means in China including the Mainland, Taiwan, and Hong Kong. Consequent to so many big arson and accidental fires in the public transport systems including trains and buses, fire safety in passenger trains is a concern. Numerical simulations with Computational Fluid Dynamics on identified fire scenarios with typical train compartments in China will be reported in this paper. The heat release rate of the first ignited item was taken as the input parameter. The mass lost rate of fuel vapor of other combustibles was estimated to predict the resultant heat release rates by the combustion models in the software. Results on air flow, velocity vectors, temperature distribution, smoke layer height, and smoke spread patterns inside the train compartment were analyzed. The results are useful for working out appropriate fire safety measures for train vehicles and determining the design fire for subway stations and railway tunnels.